The heart and soul of change : delivering what works in therapy. - Duncan, Barry, ....-; Miller, Scott D., 1958-; Wampold, Bruce E., 1948- (Washington, DC : APA, 2009)
'Updating the classic first edition of The Heart and Soul of Change, editors Duncan, Miller, Wampold, and Hubble, have created a new and enriched volume that presents the most recent research on what works in therapeutic practice, a thorough analysis of this research, and practical guidance on how a therapist can truly deliver what works in therapy. This volume examines the common factors underlying effective psychotherapy and brings the psychotherapist and the client-therapist relationship back into focus as key determinants of psychotherapy outcome. The second edition of The Heart and Soul of Change also demonstrates the power of systematic client feedback to improve effectiveness and efficiency and legitimize psychotherapy services to third party payers. In this way, psychotherapy is implemented one person at a time, based on that unique individuals perceptions of the progress and fit of the therapy and therapist. Readers familiar with the first edition will encounter the same pragmatic focus but with a larger breadth of coveragethis edition adds chapters on both youth psychotherapy and substance abuse treatment. Through reading The Heart and Soul of Change, Second Edition: Delivering What Works in Therapy clinicians of varied levels of experience will improve their understanding of what is truly therapeutic in the diverse forms of psychotherapy practiced today.'
Inhoudsopgave Chapter 1 : Introduction >I. What works and what does not : the empirical foundations for the common factors Chapter 2 : The research evidence for common factors. Models: a historically situated perspective Chapter 3 : Clients: the neglected common factor Chapter 4 : The therapeutic relationship Chapter 5 : Putting models and techniques in context Chapter 6 : Evidence-based practice: evidence or orthodoxy? Chapter 7 : Psychiatric drugs and common factors: an evaluation of risks and benefits for clinical practice >II. Delivering what works: practice-bases evidence Chapter 8 : 'Yes, it is time for clinicians to routinely monitor treatment outcome' Chapter 9 : Outcomes management, reimbursement, and the future of psychotherapy Chapter 10 : Transforming public behavioral health care: a case example of consumer-directed services recovery, and the common factors >III. Special populations Chapter 11 : Evidence-bases treatments and common factors in youth psychotherapy Chapter 12 : Common factors in couple and family therapy: must al have prizes? Chapter 13 : Whats works in substance abuse and dependence treatment >Conclusions Chapter 14 : Delivering what works